Identification and Characterization of Three New Cytochrome P450 Genes and the Use of RNA Interference to Evaluate Their Roles in Antioxidant Defense in Apis cerana cerana Fabricius - Zhang, Weixing; Chen, Wenfeng; Li, Zhenfang; Ma, Lanting; Yu, Jing; Wang, Hongfang; Liu, Zhenguo; Xu, Baohua (Frontiers in Physiology, 2018)
Abstract: Cytochrome P450s play critical roles in maintaining redox homeostasis and protecting organisms from the accumulation of toxic reactive oxygen species. The biochemical functions of the P450 family have essentially been associated with the metabolism of xenobiotics. Here, we sequenced and characterised three P450 genes, AccCYP314A1, AccCYP4AZ1, and AccCYP6AS5, from Apis cerana cerana Fabricius; these genes play a critical role in maintaining biodiversity. qPCR analysis indicated that the three genes were all predominantly expressed in the epidermis, followed by the brain and midgut. In addition, the highest expression levels were detected in the dark-eyed pupae and adult stages. The three genes were induced by temperature (4°C and 44°C), heavy metals (CdCl2 and HgCl2), pesticides (DDV, deltamethrin, and paraquat) and UV treatments. Furthermore, Western blot analysis indicated that the protein expression levels could be induced by some abiotic stressors, a result that complements the qPCR results. We analysed the silencing of these three genes and found that silencing these genes enhanced the enzymatic activities of peroxidase and catalase. Additionally, we investigated the expression of other antioxidant genes and found that some were up-regulated, while others were down-regulated, suggesting that the up-regulated genes may be involved in compensating for the silencing of AccCYP314A1, AccCYP4AZ1, and AccCYP6AS5. Our findings suggest that AccCYP314A1, AccCYP4AZ1, and AccCYP6AS5 may play very significant roles in the antioxidant defence against damage caused by reactive oxygen species.